Confinamento de partículas quânticas a curvas do espaço - Verri, Alessandra Aparecida (Universidade Federal de São Carlos, 2010)
In this work we study dimensional reductions in some quantum systems; such reductions occur due to confinement of the particle from a tube in space to a curve. Our main goal is to find the effective hamiltonian operator that describes the motion of the particle after confinement. We consider three particular situations. (1) In the first situation, we study an infinitely long tube generated by a curve with non-trivial torsion and curvature. Here the tube cross sections always have the same diameter. (2) We also study tubes in space deformed in a specific way, i.e., the diameter of the cross sections have a unique global maximum. Such tubes also have non-trivial torsion and curvature. (3) Finally, we analyze the question of which self-adjoint extension of the one-dimensional hydrogen atom would be physically relevant. We consider such atom in a three-dimensional tube and take the limit as the tube converges to the x axis, and it is shown that the Dirichlet (at the origin) extension is always obtained after such confinement.
Keywords: Teoria espectral (Matemática); Átomo de hidrogênio; Coulomb, Potencial de; Redução de dimensão; CIENCIAS EXATAS E DA TERRA::MATEMATICA